A follow-up study of social studies instruction in some selected elementary schools in Quezon City and implications for social studies instruction in the elementary schools Bangkok, Thailand - Suksuchok, Linchi 1938- (s.n.], 1973)
Social Studies teachers, principals and supervisors in 4 public and 2 private elementary schools indicated that Character Education, History, Civics, Sociology, Economics, Religion, Geography, Political Science, Anthropology, Psychology, and Philosophy. The most often used methods were discussion method, the problem-solving methods (inductive) and the unit method. Teachers used discussion, group work activities, reporting, bulletin board activities, reading library reference materials, and observation. Elementary schools in Bangkok should integrate the social studies in the upper elementary grades and use high level questioning.